Measurement of shoulder related disability: results of a validation study. Issue 8 (August 1994) - Croft, P; Pope, D; Zonca, M; O'Neill, T; Silman, A
Abstract : OBJECTIVE–To develop and validate a questionnaire to quantify disability associated with shoulder symptoms. METHODS–A set of questions relevant to shoulder symptoms from a general disability interview was developed and the questionnaire applied to a cross-sectional population survey and a prospective study of general practice attenders. Subjects included adults who reported current shoulder pain in a population survey and patients from three general practices who attended with shoulder symptoms during a six month period. The main outcome measures were: frequency of problems with daily living related to shoulder symptoms, total score on 22-item disability questionnaire, and measures of shoulder movement. RESULTS–A higher proportion (80%) of patients attending their general practitioner with shoulder symptoms had five or more disabilities compared with subjects reporting shoulder pain in a community survey (34%). The ranked frequency with which each disability was reported was similar in the two groups, although sleep disturbance was the most common problem in consulters. Self-reported disability is correlated with measures of restricted shoulder movement. CONCLUSION–This disability questionnaire was simple to complete and should prove useful for both general practice and population-based studies of shoulder pain.